VP18 Early Awareness And Alert System In Sweden: History And Current Status. (2017) - Eriksson, Irene; Wettermark, Björn; Persson, Marie; Edström, Morgan; Godman, Brian; Lindhé, Anna; Malmström, Rickard; Ramström, Helena; von Euler, Mia; Bergkvist-Christensen, Anna
Abstract : INTRODUCTION: Over the past decades, early awareness and alert (EAA) activities and systems have gained importance and become a key early Health Technology Assessment (HTA) tool. While a pioneer in HTA, Sweden had no national level EAA activities until recently. We describe the evolution and current status of the Swedish EAA System. METHODS: This was a historical analysis based on the knowledge and experience of the authors supplemented by a targeted review of published and grey literature, as well as documents produced by or relating to the Swedish EAA System. Key milestones and a description of the current state of the Swedish EAA System are presented. RESULTS: Initiatives to establish a system for the identification and assessment of emerging health technologies in Sweden date back to the 1980s. Since the 1990s, the Swedish Agency for Health Technology Assessment and Assessment of Social Services (SBU) supported the development of EuroScan and was one of its founding members. In the mid-2000s, an independent regional initiative, driven by the Stockholm Drug and Therapeutics Committee, resulted in the establishment of a regional horizon scanning unit. By 2009, this work had expanded to a collaboration between the four biggest regions in Sweden. The following year it was further expanded to the national level. Today, the Swedish EAA System carries out identification, filtration and prioritization of new drugs, early assessment of the prioritized drugs, and dissemination of the information. Its outputs are used to select new drugs for inclusion in the Swedish national process for managed introduction and follow-up. CONCLUSIONS: The Swedish EAA System started as a regional initiative and rapidly grew to become a national level activity. An important feature of the system today is its complete integration into the national process for managed introduction and follow-up of new drugs. The system will continue to evolve as a response both to the changing landscape of health innovations and to new policy initiatives at the regional, national and international levels.